Identification and Expression Profiles Reveal Key Myelocytomatosis (MYC) Involved in Drought, Chilling, and Salt Tolerance in Solanum lycopersicum - Chenchen Kang; Na Cui; Baozhen Zhao; Qingdao Zou; Yiming Zhang; Shiquan Bi; Zhongfen Wu; Meini Shao; Bo Qu (Horticulturae)
Tomato (Solanum lycopersicum) is a vital crop in China, yet its growth and quality are compromised by environmental stresses. This study investigated the role of myelocytomatosis (MYC) transcription factors (SlMYCs) in tomato stress tolerance. We identified 23 potential SlMYC genes and analyzed their physicochemical properties, evolutionary relationships, gene structures, conserved domains, expression profiles, interaction networks, promoter sequences, and 3D models using bioinformatics. Phylogenetic analysis classified the SlMYCs into three groups with similar structural characteristics. Protein interaction networks revealed significant connections between SlMYCs and proteins involved in drought, chilling, and salt tolerance, particularly emphasizing the jasmonic acid signaling pathway. Experimental treatments with methyl jasmonate (MeJA) and simulated stress conditions showed that several SlMYC genes were responsive to these stimuli, with SlMYC1 and SlMYC2 demonstrating consistent expression patterns across various tissues. Further network analyses and molecular docking studies indicated potential binding interactions for these two genes. The findings confirmed that SlMYC1 and SlMYC2 contributed to tomato’s abiotic stress tolerance, highlighting their potential for breeding programs aimed at improving stress resilience in tomato varieties. This research laid the groundwork for enhancing tomato varieties under environmental stressors.